The Holocaust in Hungary : seventy years later - Kovacs, Andras; Braham, Randolph L.; Kovács, András, 1947- (Central European University Press, 2016)
The studies reflect on the anti-Jewish atmosphere in Hungary during the interwar period; analyze the decision-making process that led to the deportations, and the options left open to the Hungarian government.